Restoration of the service and loss minimization in electrical distribution systems - Ganney Poorna Chandra Rao; Pallikonda Ravi Babu (Institute of Advanced Engineering and Science, 2023)
Restoration of service during faults to healthy zones and the minimization of true or real power losses are the main aspects of the satisfactory operation of an electrical distribution system (EDS). These objectives can be achieved with artificially intelligent optimisation techniques through electrical distribution system reconfiguration. The restoration of service is an important part of ensuring a stable power supply. If there is a fault with the EDS, the damaged zone is separated, and the healthy system is restored without breaching limitations. In the distribution system, ohmic losses are 25-35%. It is essential to reconfigure the system toreduce these losses. In this paper, a hybrid artificial rabbits’optimisation and improved mayfly optimisation (ARO-IMO) technique is adopted for restoration of serviceand loss minimization. The method being suggested will be carried out on an IEEE 4-feeder network for restoration of service and on IEEE 33 and69 radial distribution networks (RDN) for diminution of losses.